Evaluation of a Digital Literacy Program Through E-Business Among Micro, Small, And Medium Enterprises (Msmes) in the Special Region of Yogyakarta - Mia Aulia; M. Fajrus Shodiq (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study aims to evaluate the digital literacy program through E-Business managed by the DIY Communication and Informatics Office based on William N. Dunn’s six evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The study also identifies supporting and inhibiting factors in program implementation. Using a descriptive evaluative qualitative method, the research focuses on the UMKM digital literacy program in the Special Region of Yogyakarta. The results show that the program is a relevant strategic policy for supporting UMKM digital transformation and community economic empowerment. Supporting factors include government policy support, internet infrastructure, relevant materials, and participant enthusiasm. Meanwhile, inhibiting factors include limited resources, lack of continuous mentoring, and participant selection that is not fully targeted. To optimize program sustainability, improvements are needed in participant selection, follow-up training, post-training assistance, access expansion, and evaluation systems. These improvements are expected to enhance the competitiveness, productivity, and welfare of UMKM in Yogyakarta